Heat treatment and hot isostatic pressing effects on laser powder bed fusion Al-10Si-0.4 Mg microstructure, fatigue crack growth mechanisms, and ultrasonic fatigue behavior - Piette, Timothy D.; Spangenberger, Anthony G.; Warren, Robert J.; Lados, Diana A. (Engineering fracture mechanics, 2025)
•Single-source fatigue analysis dataset for heat treated & as-built LPBF Al-10Si-Mg.•HIP + T6 tensile, fatigue, and FCG properties superior to other LPBF and cast cases.•Ultrasonic fatigue shows fisheye initiation and surface-to-internal change in VHCF. The application of additive manufacturing to safety–critical components subject to cyclic loading requires thorough measurement of fatigue properties and development of post-processing treatments that remediate non-optimal, as-fabricated microstructures. In this study, microstructures, tensile properties, fatigue crack growth response, and ultrasonic fatigue behavior of laser powder bed manufactured Al-10Si-0.4 Mg were systematically investigated in two orientations with respect to the build direction and compared in as-fabricated, stress relieved, T6, and HIP + T6 conditions, as well as with a conventionally cast counterpart. Heat treatment caused fragmentation (stress relieved case) and coarsening (T6 and HIP + T6 cases) of the eutectic silicon network, most significantly along melt pool and grain boundaries. Compared to the as-fabricated condition, stress relief increased ductility and decreased yield and ultimate tensile strengths, while solutionizing and aging greatly increased ductility, increased yield strength, and decreased ultimate tensile strength. In the as-fabricated condition, the fatigue crack growth response is affected by growth orientation relative to the build direction, however after heat treatment, this orientation dependance is lost and threshold values increased (as much as 400 %) due to activation of roughness-induced closure. In addition, ultrasonic fatigue studies showed that fatigue life in the high to very high cycle fatigue regime following heat treatment can either increase (HIP + T6) or decrease (T6) fatigue lives relative to the as-fabricated condition. Overall, solutionizing and aging heat treatments serve to neutralize the anisotropic mechanical behavior of the as-fabricated material, while decreasing tensile strength, increasing yield strength, elongation, fatigue crack growth threshold, and having mixed effects on fatigue lifetimes.